Copper-based metal-organic framework materials, methods of making and applications thereof

CN119613741BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311177184.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2026-10-16
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

[0006]目前二维Cu-BTC的制备方法大多需要借助表面活性剂等定向排列配体,使金属离子和配体定向聚合;或通过特殊结构的配体控制晶体生长方向;或通过物理或化学方法将三维体相层状材料分层,形成二维纳米层,存在原料复杂、条件苛刻等不足,亟需开发新的合成策略

Benefits of technology

[0018] The beneficial effects of the present invention through the above technical solution include:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613741B_ABST
    Figure CN119613741B_ABST
Patent Text Reader

Abstract

The application relates to the preparation field of metal organic framework materials, and discloses a copper-based metal organic framework material and a preparation method and application thereof. The copper-based metal organic framework material has a nanolayered morphology, and the nanolayers are distributed in a petal shape; wherein the metal element in the metal organic framework material is copper; and the organic ligand in the metal organic framework material is uniform benzenetricarboxylic acid. The copper-based metal organic framework material is used in an electrocatalytic reduction carbon dioxide reaction, and has high ethylene and ethanol Faraday efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal-organic framework material preparation, specifically to a copper-based metal-organic framework material, its preparation method, and its application. Background Technology

[0002] Global climate change is a major survival challenge facing humanity. Capturing and converting carbon dioxide using chemical methods with renewable and clean energy is a highly promising approach. Electrocatalytic carbon dioxide reduction technology converts carbon dioxide into chemicals such as carbon monoxide, formic acid, methane, ethylene, ethanol, acetic acid, and n-propanol using renewable electricity, thus realizing the resource utilization of carbon dioxide. Ethylene and ethanol, with their high energy density and market value, are ideal products of electrocatalytic carbon dioxide reduction. However, the current lack of high-performance catalysts to support the development of electrocatalytic carbon dioxide reduction technology makes the development of high-performance catalysts of great significance.

[0003] Metal-organic frameworks (MOFs) are zeolite-like materials formed by the complexation of organic ligands and metal ions. They possess molecular / atomic-level catalytic active centers, high porosity, large surface area, high loading capacity, and easily tunable structures, making them among the most promising electrocatalytic catalysts for carbon dioxide reduction. For example, copper-based MOFs (Cu-BTC) and their derivatives are frequently used for electrocatalytic carbon dioxide reduction. CN112301375A uses Cu-BTC for the electrocatalytic reduction of carbon dioxide, achieving a Faradaic efficiency of up to 30% for ethylene and less than 10% for ethanol. Wolfgang Schuhmann et al. (DOI: 10.1002 / anie.202108313) used carbonized and hydrophobically treated Cu-BTC as an electrocatalyst for carbon dioxide reduction, achieving a combined Faradaic efficiency of less than 50% for ethylene and ethanol. Boon Siang Yeo et al. (DOI:10.1021 / cs502128q) used electrodeposition to prepare cuprous oxide thin films as electrocatalysts for carbon dioxide reduction, and the sum of the Faraday efficiencies for ethylene and ethanol was less than 50%.

[0004] From a microstructural perspective, the structural units of existing Cu-BTC technologies are mostly octahedral micron-sized bulk materials with pore sizes of approximately 1 nm. This is unfavorable for mass transfer and exposure of active sites, resulting in low pore utilization. However, the electrocatalytic carbon dioxide reduction reaction is a gas-liquid-solid three-phase interface reaction, requiring a catalyst with highly exposed active sites to facilitate the rapid adsorption of flowing carbon dioxide gas onto the catalyst surface for reaction. Two-dimensional MOF materials expose abundant active centers and shorten diffusion distances, effectively overcoming the shortcomings of bulk MOFs.

[0005] Hua Chun Zeng et al. (DOI: 10.1002 / adfm.201505380) used polyvinylpyrrolidone to regulate the arrangement of BTC, and used Cu2O, which has very low solubility, as a copper source. The slowly released copper ions and BTC were directionally coordinated and polymerized to prepare nanolayers with a thickness of 30 nm to 55 nm. CN108559101A disclosed the use of alkali to treat the bulk Cu-BTC, breaking some coordination bonds to form nanolayers of several hundred nanometers. Jun Lin et al. (DOI: 10.1021 / acs.cgd.8b01695) dissolved copper ions in oleic acid to encapsulate the copper ions, which then reacted with BTC in the aqueous phase at the two-phase interface, inhibiting the crystal growth rate and polymerization direction, and preparing spherical nanoparticles of 30 nm to 140 nm.

[0006] Currently, most methods for preparing two-dimensional Cu-BTC require the use of surfactants or other directionally aligned ligands to induce the directional polymerization of metal ions and ligands; or the control of crystal growth direction through ligands with special structures; or the layering of three-dimensional bulk materials into two-dimensional nanolayers through physical or chemical methods. These methods suffer from drawbacks such as complex raw materials and harsh conditions, and there is an urgent need to develop new synthesis strategies. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems existing in the prior art and provide a copper-based metal-organic framework material, its preparation method, and its applications. When the copper-based metal-organic framework material of this invention is used in the electrocatalytic reduction of carbon dioxide, it exhibits high Faraday efficiency for ethylene and ethanol.

[0008] To achieve the above objectives, the present invention provides a copper-based metal-organic framework material, wherein the metal-organic framework material has a nanolayered morphology and the nanolayers are distributed in a petal-like pattern.

[0009] The metal element in the metal-organic framework material is copper;

[0010] The organic ligand in the metal-organic framework material is pyromellitic acid.

[0011] A second aspect of this invention provides a method for preparing a copper-based metal-organic framework material, the method comprising the following steps:

[0012] (1) A methanol solution of copper nitrate 2,5-hydrate and a methanol solution of trimesic acid are mixed to obtain a mixture; under closed conditions, the mixture is subjected to a hydrothermal reaction in a reaction vessel to obtain a solid product;

[0013] (2) The solid product is washed and dried;

[0014] The volume of the mixture is 15-50% of the volume of the reaction vessel.

[0015] Preferably, the concentration of the methanol solution of copper nitrate 2,5-hydrate is 5-40 mg / mL, more preferably 20-38 mg / mL.

[0016] Preferably, the concentration of the methanol solution of pyromellitic acid is 2-15 mg / mL, more preferably 8-15 mg / mL.

[0017] The third aspect of this invention provides the application of the copper-based metal-organic framework material described in the first aspect or the copper-based metal-organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide.

[0018] The beneficial effects of the present invention through the above technical solution include:

[0019] The copper-based metal-organic framework material with a two-dimensional nanolayer morphology arranged in a petal-like pattern provided by this invention has a high electrochemical active area and catalytic activity, and exhibits high Faraday efficiency for ethylene and ethanol when applied to the electrocatalytic reduction of carbon dioxide.

[0020] The method for preparing copper-based metal-organic framework materials provided by this invention can prepare petal-shaped two-dimensional nanolayers through a simple one-step solvothermal method. The preparation process avoids the use of surfactants or methods such as two-phase interfaces and insoluble precursors to reduce the growth rate. The operation is simple, the preparation conditions are mild, the cost is low, the synthesis method is efficient, and it is easy to scale up, which has great application advantages and prospects. Attached Figure Description

[0021] Figure 1 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Example 1 of the present invention;

[0022] Figure 2 These are the X-ray diffraction patterns of the copper-based metal-organic framework materials prepared in Example 1 and Comparative Example 1 of this invention.

[0023] Figure 3 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 1 of the present invention.

[0024] Figure 4 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 2 of the present invention.

[0025] Figure 5 This is a scanning electron microscope image of the copper-based metal-organic framework material prepared in Comparative Example 3 of this invention. Detailed Implementation

[0026] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0027] The present invention provides a copper-based metal-organic framework material, wherein the metal-organic framework material has a nanolayered morphology and the nanolayers are distributed in a petal-like pattern;

[0028] The metal element in the metal-organic framework material is copper;

[0029] The organic ligand in the metal-organic framework material is pyromellitic acid.

[0030] In this invention, the petal-shaped distribution of the nanolayers means that the nanolayers are stacked on top of each other and radiate outward in a petal-like shape.

[0031] The morphology of the metal-organic framework material described in this invention was measured using a scanning electron microscope.

[0032] According to the present invention, preferably, the metal-organic framework material exhibits characteristic peaks at 2θ values ​​of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2°, and 42.7°±0.2° as characterized by X-ray diffraction.

[0033] As can be seen from the XRD pattern, compared with the metal-organic framework material of Comparative Example 1, the metal-organic framework material of this invention has characteristic peaks at 2θ positions of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2°, and 42.7°±0.2°, which can be used as a reference. Figure 2 The use of metal-organic framework materials with this microstructure is beneficial for improving the Faraday efficiency of ethylene and ethanol in the subsequent electrocatalytic reduction of carbon dioxide.

[0034] According to the present invention, preferably, the thickness of the nanolayer is 20-90 nm, more preferably 20-50 nm. This indicates that the copper-based metal-organic framework material of the present invention has a uniformly distributed two-dimensional nanolayer with concentrated thickness. Compared with the micron-scale bulk Cu-BTC, the copper-based metal-organic framework material of the present invention has more exposed active sites and can shorten the mass transfer distance, which is beneficial for improving the Faraday efficiency of ethylene and ethanol in the electrocatalytic reduction of carbon dioxide.

[0035] The thickness of the nanolayer described in this invention was obtained by scanning electron microscopy.

[0036] A second aspect of this invention provides a method for preparing a copper-based metal-organic framework material, the method comprising the following steps:

[0037] (1) A methanol solution of copper nitrate 2,5-hydrate and a methanol solution of trimesic acid are mixed to obtain a mixture; under closed conditions, the mixture is subjected to a hydrothermal reaction in a reaction vessel to obtain a solid product;

[0038] (2) The solid product is washed and dried;

[0039] The volume of the mixture is 15-50% of the volume of the reaction vessel.

[0040] In the preparation method provided by this invention, a specific methanol solution of copper nitrate 2,5-hydrate and a methanol solution of trimesic acid are used, and the filling degree of the mixture in the reaction vessel is controlled to prepare the petal-shaped two-dimensional nanolayer described in the previous aspect of this invention. The petal-shaped two-dimensional nanolayer of this invention has a high electrochemical active area and catalytic activity, and exhibits high Faraday efficiency in the electrocatalytic reduction of carbon dioxide for ethylene and ethanol.

[0041] The present invention does not particularly limit the reaction vessel for the hydrothermal reaction described in step (1), and it can be any vessel capable of realizing the hydrothermal reaction. The present invention uses a conventional hydrothermal reactor with a polytetrafluoroethylene liner as an example.

[0042] In existing technologies, under the premise of ensuring reaction safety, the larger the volume of the mixture in the reaction vessel, the better, in order to obtain more metal-organic framework materials. Typically, the volume of the mixture is 70-80% of the reaction vessel volume. However, in this invention, the volume of the mixture is 15-50% of the reaction vessel volume, preferably 20-40%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value within any two of these ranges. This preferred embodiment facilitates the reduction of coordinated divalent copper nodes to cuprous metals by methanol vapor, leading to the formation of a unique two-dimensional layered nanostructure and a new crystal structure after recrystallization.

[0043] According to the present invention, preferably, the concentration of the methanol solution of copper nitrate 2,5-hydrate is 5-40 mg / mL, more preferably 20-38 mg / mL. For example, it can be 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL, 20 mg / mL, 22 mg / mL, 24 mg / mL, 26 mg / mL, 28 mg / mL, 30 mg / mL, 32 mg / mL, 34 mg / mL, 36 mg / mL, 38 mg / mL, 40 mg / mL, and any value within any two of these ranges. This preferred embodiment facilitates obtaining the copper-based metal-organic framework material with the morphology and distribution described in the present invention.

[0044] According to the present invention, preferably, the concentration of the methanol solution of trimesic acid is 2-15 mg / mL, more preferably 8-15 mg / mL, for example, it can be 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, and any value within any two of these ranges. This preferred embodiment is advantageous for obtaining the copper-based metal-organic framework material with the morphology and distribution described in the present invention.

[0045] According to the present invention, preferably, the mass ratio of copper nitrate 2,5-hydrate to trimesic acid is 0.4-6, more preferably 1.5-3, for example, it can be 0.4:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, and any value within any range of any two of these values. This preferred embodiment is more advantageous for obtaining the copper-based metal-organic framework material with the morphology and distribution described in the present invention.

[0046] The present invention does not have any particular limitation on the mixing in step (1), and can be carried out with reference to conventional methods in the art.

[0047] According to the present invention, preferably, the conditions for the hydrothermal reaction in step (1) include: a temperature of 80-130℃, preferably 110-125℃, for example, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, and any value within the range formed by any two of these values; and a time of 12-60h, preferably 18-36h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h, 50h, 52h, 54h, 56h, 58h, 60h, and any value within the range formed by any two of these values. This preferred embodiment is beneficial to improving the Faraday efficiency of ethylene and ethanol in the subsequent electrocatalytic reduction of carbon dioxide.

[0048] Preferably, the method further includes: performing solid-liquid separation on the product of the hydrothermal reaction in step (1) to obtain a solid product.

[0049] This invention does not impose any particular limitation on the method of solid-liquid separation; conventional techniques in the field can be used.

[0050] The present invention does not particularly limit the specific conditions for washing, and can be carried out according to the methods in the art, washing until the solution is clear.

[0051] The present invention allows for a wide range of choices of detergents for washing, which can be conventional choices in the art. Preferably, the detergent is selected from at least one of water, methanol, ethanol, and acetone.

[0052] According to one specific embodiment of the present invention, the solid product is washed with a detergent and soaked in the detergent for 1-2 days, during which time the anhydrous ethanol is replaced 2-5 times. This preferred embodiment facilitates the thorough removal of unreacted substances.

[0053] The present invention does not particularly limit the drying conditions in step (2), and can be carried out according to methods in the art. Preferably, the drying is vacuum drying.

[0054] Preferably, the method does not involve the addition of a surfactant. The surfactant can be any conventional choice in the art, and will not be described in detail here.

[0055] By adopting this preferred embodiment, the preparation method provided by the present invention avoids substances such as surfactants, is simple to operate, has mild preparation conditions, low cost, high efficiency in synthesis, and is easy to scale up, thus having great application advantages and prospects.

[0056] The third aspect of this invention provides the application of the copper-based metal-organic framework material described in the first aspect or the copper-based metal-organic framework material prepared by the preparation method described in the second aspect in the electrocatalytic reduction of carbon dioxide.

[0057] The present invention does not impose any particular limitations on the conditions for the electrocatalytic reduction of carbon dioxide reaction, and can be carried out in accordance with conventional methods in the art.

[0058] The present invention will be described in detail below through embodiments.

[0059] In the following embodiments, the product detection method is as follows:

[0060] Gas product analysis: A gas chromatograph (Agilent 7890B) was used, equipped with a flame ionization detector and a thermal conductivity detector. The thermal conductivity detector detected hydrogen, and carbon monoxide was detected by the flame ionization detector after being hydrogenated in a methane converter.

[0061] Liquid product analysis: Using proton nuclear magnetic resonance (Agilent 700M), the cathode electrolyte was taken, heavy water was added to lock the field, and dimethyl sulfoxide was used as an internal standard.

[0062] Example 1

[0063] Dissolve 0.451 g of copper nitrate 2,5-hydrate in 15 mL of methanol to prepare solution A; dissolve 0.220 g of trimesic acid in 15 mL of methanol to prepare solution B; mix solutions A and B to obtain a mixed solution. Transfer the mixed solution to a 100 mL hydrothermal reactor lined with a stainless steel jacket and react at 120 °C for 24 h, then cool to room temperature. Separate the reaction products from the hydrothermal reaction to obtain a solid product.

[0064] The solid product was washed with anhydrous ethanol and then soaked in anhydrous ethanol for 2 days, with the ethanol being replaced 4 times during the soaking period. The washed material was then vacuum dried at 80°C for 12 hours to obtain a copper-based metal-organic framework material.

[0065] An exemplary SEM image of the copper-based metal-organic framework material described in Example 1 is given, as follows: Figure 1 As shown, the copper-based metal-organic framework material exhibits a nanolayered morphology, such as... Figure 1 As shown in Figure b, the thickness of the nanolayer is 30-50 nm, and the nanolayer is distributed in a petal-like pattern, as... Figure 1 As shown in Figure a.

[0066] An exemplary XRD pattern of the copper-based metal-organic framework material described in Example 1 is given, as follows: Figure 2 As shown, compared with Comparative Example 1, the petal-shaped Cu-BTC of Example 1 exhibits diffraction peaks at diffraction angles of 12.5°, 21.6°, 25.6°, 32°, 33.5°, 34.4°, 36°, 41.6°, and 42.7°, indicating the formation of a new phase and a significant change in the crystal structure of the petal-shaped Cu-BTC of Example 1.

[0067] Example 2

[0068] Dissolve 0.451 g of copper nitrate 2,5-hydrate in 15 mL of methanol to prepare solution A; dissolve 0.174 g of trimesic acid in 15 mL of methanol to prepare solution B; mix solutions A and B to obtain a mixed solution. Transfer the mixed solution to a 100 mL hydrothermal reactor lined with a stainless steel jacket and react at 110 °C for 24 h, then cool to room temperature. Separate the reaction products from the hydrothermal reaction to obtain a solid product.

[0069] The solid product was washed with anhydrous ethanol and then soaked in anhydrous ethanol for 2 days, with the ethanol being replaced 4 times during the soaking period. The washed material was then vacuum dried at 80°C for 12 hours to obtain a copper-based metal-organic framework material with a nanolayer thickness of 30-50 nm.

[0070] Example 3

[0071] Dissolve 0.400 g of copper nitrate 2,5-hydrate in 20 mL of methanol to prepare solution A; dissolve 0.161 g of trimesic acid in 20 mL of methanol to prepare solution B; mix solutions A and B to obtain a mixed solution. Transfer the mixed solution to a 100 mL hydrothermal reactor lined with a stainless steel jacket and react at 110 °C for 36 h, then cool to room temperature. Separate the reaction products from the hydrothermal reaction to obtain a solid product.

[0072] The solid product was washed with anhydrous ethanol and then soaked in anhydrous ethanol for 2 days, with the ethanol being replaced 4 times during the soaking period. The washed material was then vacuum dried at 80°C for 12 hours to obtain a copper-based metal-organic framework material with a nanolayer thickness of 30-50 nm.

[0073] Example 4

[0074] The procedure was carried out according to Example 1, except that 0.206 g of copper nitrate 2,5-hydrate was dissolved in 8 mL of methanol to prepare solution A; 0.101 g of trimesic acid was dissolved in 8 mL of methanol to prepare solution B; solutions A and B were mixed to obtain a mixed solution. The volume of the mixed solution was 16% of the reaction vessel volume, resulting in a copper-based metal-organic framework material with a nanolayer thickness of 30-50 nm.

[0075] Example 5

[0076] The method of Example 1 was followed, except that the amount of 2,5-hydrated nitric acid used was 0.3g, and a copper-based metal-organic framework material was obtained with a nanolayer thickness of 30-50nm.

[0077] Example 6

[0078] The method of Example 1 was followed, except that 0.42 g of pyromellitic acid was used to obtain a copper-based metal-organic framework material with a nanolayer thickness of 30-50 nm.

[0079] Example 7

[0080] The method was carried out according to Example 1, except that the hydrothermal reaction temperature was 130°C, and a copper-based metal-organic framework material was obtained with a nanolayer thickness of 25-45 nm.

[0081] Example 8

[0082] The method of Example 1 was followed, except that the hydrothermal reaction time was 12 hours, resulting in a copper-based metal-organic framework material with a nanolayer thickness of 30-50 nm.

[0083] Comparative Example 1

[0084] Copper-based metal-organic framework materials prepared by existing technology

[0085] Dissolve 2.952 g of copper nitrate trihydrate in 40.5 mL of ethanol-water solution (ethanol:water volume ratio 1:1) to prepare solution A; dissolve 1.713 g of trimesic acid in 40.5 mL of ethanol-water solution (ethanol:water volume ratio 1:1) to prepare solution B; mix solutions A and B at room temperature and transfer them to a 100 mL reaction vessel lined with polytetrafluoroethylene and stainless steel jacket, and react at 120 °C for 24 h. After the reaction is completed, cool to room temperature and separate the reaction products of the hydrothermal reaction to obtain the solid product.

[0086] The solid product was washed with anhydrous ethanol and then soaked in anhydrous ethanol for two days, with the ethanol being replaced several times during the soaking period. The washed material was then vacuum dried at 80°C for 12 hours to obtain a copper-based metal-organic framework material, denoted as Cu-BTC.

[0087] The scanning electron microscope image of Comparative Example 1 is as follows: Figure 3 As shown, the resulting product is a classic octahedral block.

[0088] The XRD pattern of the copper-based metal-organic framework material described in Comparative Example 1 is shown below. Figure 2 As shown, it is consistent with the Cu-BTC crystal structure reported in existing literature.

[0089] Comparative Example 2

[0090] The method of Example 1 was followed, except that instead of using copper nitrate 2,5-hydrate, an equal mass of copper nitrate trihydrate was used to obtain a copper-based metal-organic framework material.

[0091] SEM images of the copper-based metal-organic framework material described in Comparative Example 2, as shown below. Figure 4 As shown. You can see Figure 4 The product shown consists of a small number of nanolayers and a large number of bulk aggregates, and does not exhibit the characteristics of the product prepared in Example 1. Figure 1 The uniform, petal-shaped two-dimensional nanolayer structure shown is illustrated.

[0092] Comparative Example 3

[0093] The procedure was carried out according to Example 1, except that 0.644 g of copper nitrate 2,5-hydrate was dissolved in 25 mL of ethanol to prepare solution A, and 0.314 g of trimesic acid was dissolved in 25 mL of ethanol to prepare solution B, thus obtaining a copper-based metal-organic framework material.

[0094] SEM images of the copper-based metal-organic framework material described in Comparative Example 3, as shown below. Figure 5 As shown, the resulting product is a micron-sized bulk composed of nanoparticles aggregated together.

[0095] Test Example 1

[0096] 5 mg of the copper-based metal-organic framework material prepared in the examples and comparative examples were dispersed in 500 μL of anhydrous ethanol and sonicated for 15 min. Then, 20 μL of Nafion perfluorosulfonic acid resin solution was added, and the mixture was sonicated for 30 min to obtain a mixed solution. 60 μL of this mixed solution was drop-coated onto 1 cm × 1 cm carbon paper (Toray hydrophobic carbon paper from Japan) and dried at 40 °C to obtain a working electrode loaded with the copper-based metal-organic framework material, wherein the loading of the copper-based metal-organic framework material was 0.58 mg. Using a 1 cm × 1 cm platinum sheet as the counter electrode and Ag / AgCl (saturated KCl) as the reference electrode, a proton exchange membrane (Nafion 117) separated the anode and cathode chambers, allowing selective passage of cations from the anode into the cathode chamber. Electrocatalytic carbon dioxide reduction was tested in an H-type electrolytic cell with the above-mentioned three-electrode system using 0.1 M KHCO3 solution as the electrolyte. Using pure carbon dioxide gas as the reactant, the gas flow rate was controlled at 50 mL / min by a gas mass flow meter. The results of the reaction for 60 min at a potential of -1.6 (V vs. reversible hydrogen electrode) are shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] As can be seen from the results in Table 1, the copper-based metal-organic framework material provided by this invention exhibits significantly higher Faraday efficiencies for ethylene and ethanol when applied to the electrocatalytic carbon dioxide reduction reaction.

[0101] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A copper-based metal-organic framework material, characterized in that, The metal-organic framework material has a nanolayered morphology, and the nanolayers are distributed in a petal-like pattern; the petal-like distribution of the nanolayers means that the nanolayers are stacked on top of each other and radiate outward in a petal-like pattern. The metal element in the metal-organic framework material is copper; The organic ligand in the metal-organic framework material is pyromellitic acid; X-ray diffraction analysis revealed that the metal-organic framework material exhibited characteristic peaks at 2θ values ​​of 12.5°±0.2°, 21.6°±0.2°, 25.6°±0.2°, 32°±0.2°, 33.5°±0.2°, 34.4°±0.2°, 36°±0.2°, 41.6°±0.2°, and 42.7°±0.2°.

2. The metal-organic framework material according to claim 1, wherein, The thickness of the nanolayer is 20-90 nm.

3. The metal-organic framework material according to claim 2, wherein, The thickness of the nanolayer is 20-50 nm.

4. A method for preparing a copper-based metal-organic framework material according to any one of claims 1-3, the method comprising the following steps: (1) A methanol solution of copper nitrate 2,5-hydrate and a methanol solution of trimesic acid are mixed to obtain a mixture; under closed conditions, the mixture is subjected to a hydrothermal reaction in a reaction vessel to obtain a solid product; (2) The solid product is washed and dried; The volume of the mixture is 15-50% of the volume of the reaction vessel.

5. The preparation method according to claim 4, wherein, The volume of the mixture is 20-40% of the volume of the reaction vessel.

6. The preparation method according to claim 4, wherein, The concentration of a methanol solution of copper nitrate hydrate is 5-40 mg / mL; And / or, the concentration of the methanol solution of pyromellitic acid is 2-15 mg / mL.

7. The preparation method according to claim 6, wherein, The concentration of a methanol solution of copper nitrate hydrate is 20-38 mg / mL; And / or, the concentration of the methanol solution of pyromellitic acid is 8-15 mg / mL.

8. The preparation method according to claim 4, wherein, The mass ratio of 2,5-hydrated copper nitrate to trimesic acid is 0.4-6.

9. The preparation method according to claim 8, wherein, The mass ratio of copper nitrate hydrate to triphenyl benzoic acid is 1.5-3.

10. The preparation method according to any one of claims 4-9, wherein, The conditions for the hydrothermal reaction in step (1) include: a temperature of 80-130℃ and a time of 12-60h.

11. The preparation method according to claim 10, wherein, The conditions for the hydrothermal reaction in step (1) include: a temperature of 110-125℃ and a time of 18-36h.

12. The preparation method according to any one of claims 4-9, wherein, The washing agent is selected from at least one of water, methanol, ethanol and acetone.

13. The application of the copper-based metal-organic framework material according to any one of claims 1-3 or the copper-based metal-organic framework material prepared by any one of claims 4-12 in the electrocatalytic reduction of carbon dioxide.

Citation Information

Patent Citations

  • Method for preparing two-dimensional sheet-shaped Cu-MOF (Metal Organic Framework) material

    CN108559101A

  • Graphene-metal organic framework composite material modified electrode preparation method

    CN107703195A

  • Metal organic framework composite material and preparation method and application thereof

    CN111266089A